Studying the Different Forms of Metaphor in the Sayings of our Prophet (Peace Be Upon Him) - Mohammad Ibrahim Khalifa Shushtari; Ali Akbar Noreside (دراسات في اللغة العربيّة وآدابها)
Metaphor is one of the superior literary styles of Arabs and is a criterion for identifying and measuring their astuteness and skillfulness. Some of the beauty in speeches or sentences is related to metaphor. Without any doubt, the messenger of God (Peace Be Upon Him) was at the peak eloquence. He was speaking to the Arab tribes in their own language and accent in the possible articulate and eloquent way. The aim of this paper is to study the style of metaphor and its manifestation in the speeching and sayings of the prophet (Peace Be Upon Him). It wants to portray a small piece of the eloquence of our prophet. Another aim of this paper is to find a proper answer for the following questions: what is the position of metaphor in saying of prophet (Peace Be upon Him)? What kind of styles of metaphor was used by him? What is the practical role of metaphor in conveying the meaning and making it close to the mind of the addressed person? Is it that our prophet has been under the influence of the Quran in his words and, in case of positive answer, how much was the influence? Our method in this research is choosing some of the traditions (Hadiths) of our prophet in which he has used metaphor and portrayings these metaphors. We have tried to complete what has been said and provide what has not been said.